MASS TRANSFER DURING ANDALUSITE REPLACEMENT BY KYANITE IN AL- AND FE-RICH METAPELITES IN THE YENISEI RANGE - Likhanov I.I.; Reverdatto V.V. (My University, 2002)
Information on the textures, mineralogy, and chemistry of rocks was used to study the behavior of material during dislocation metamorphism of Al- and Fe-rich metapelites in the Yenisei Range. Metamorphism of the kyanite-sillimanite type was associated with rock deformations. The replacement of andalusite by kyanite and development of new microtextures and mineral assemblages were related to an increase in the lithostatic pressure near the Panimbinskii overthrust. The compositions of minerals and their volumetric proportions in the rocks were utilized to calculate the equations of chemical reactions responsible for the origin of Ky-St-Ms-Qtz pseudomorphs and mineralogical transformations that brought about staurolite and garnet crystallization. Analysis of mass balance and changes in the mineralogical composition indicate that the general scheme of mass transfer during andalusite replacement by kyanite is the sum of two isochemical local reactions. It is determined that the minimum volume within which mass transfer proceeded and the full balance of major components between the reacting phases was maintained did not exceed ∼1.6 ± 0.4 cm3. As the deformations became more intense, the minimum volume increased due to the full pseudomorph replacement of andalusite crystals. Our results are in agreement with the estimated mass-transfer scale during metamorphic reactions in metapelites under similar P-T metamorphic conditions elsewhere.